2019
DOI: 10.1016/j.amjcard.2019.05.026
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Prophylactic Implantable Cardioverter Defibrillator Implantation in Asymptomatic Heart Failure Patients With a Reduced Ejection Fraction

Abstract: Recommendations for prophylactic implantable cardioverter defibrillator (ICD) implantation in asymptomatic heart failure patients with a reduced left ventricular ejection fraction (LVEF) differ between guidelines. Evidence on the risk of appropriate device therapy (ADT) and death in New York Heart Association (NYHA) class I patients is scarce. Aim of this study is to evaluate ADT and mortality in NYHA-I primary prevention ICD patients with a LVEF ≤35%. A retrospective cohort was studied, including 572 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Primary prevention ICD use was associated with reduced risk of 1-year and 5-year all-cause death, and the association between ICD use and all-cause mortality was consistent in patients with versus without ischemic heart disease [2]. Furthermore, van der Lingen et al even found that primary prevention in New York Heart Association (NYHA) class I ICD patients showed a higher incidence of appropriate device therapy compared with NYHA II and III ICD patients [3]. These results strongly suggest that primary prevention NYHA I patients with a left ventricular ejection fraction 35 % are likely to benefit from ICD therapy and should not be excluded from a potentially lifesaving therapy [3].…”
Section: Dear Editormentioning
confidence: 99%
See 4 more Smart Citations
“…Primary prevention ICD use was associated with reduced risk of 1-year and 5-year all-cause death, and the association between ICD use and all-cause mortality was consistent in patients with versus without ischemic heart disease [2]. Furthermore, van der Lingen et al even found that primary prevention in New York Heart Association (NYHA) class I ICD patients showed a higher incidence of appropriate device therapy compared with NYHA II and III ICD patients [3]. These results strongly suggest that primary prevention NYHA I patients with a left ventricular ejection fraction 35 % are likely to benefit from ICD therapy and should not be excluded from a potentially lifesaving therapy [3].…”
Section: Dear Editormentioning
confidence: 99%
“…It is well established in current literature that tremendous success has been achieved over the last decades in the management of SCD in patients with HF by the use of ICD [4]. Notably, in ischemic cardiomyopathy patients, the clinical benefit from ICD is well-stablished [2][3][4][5]. Dramatic changes in medical treatment, though, have rendered a reevaluation of the role of devices for primary prevention of SCD in patients receiving up-to-date optimal care imperative [4].…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations